The Political Games of Media Investors and the Effects of Democracy Health - Mukhijab; Usman, Sunyoto; Azca, M. Najib; Yamin, Muhammad Nurul; Masrizal (International Journal of Psychosocial Rehabilitation, 2020)
This article examines research on investors, power, and the media, to understand the political practices of media investors in political contestation in Indonesia, and the health problems of democracy that occur as a result of using the media as a tool for a power struggle. Using a qualitative text analysis method with a discourse analysis of social cognition, the analysis of the findings of this research includes two levels, namely the level of the text and the social context. The findings of this study showed that the presence of media investors in the political arena threatens the health problem of democracy. 1). As a media person, media investors want a top-down model of the narrative of democracy applied through authoritarian authorities. 2). Media financiers intervene in ownership of media affiliated with ownership, and economic interventions on competitors' media so that the narrative of democracy matches their tastes. 3). Ownership affiliated media are trapped in the flow of game and investor solidarity, while the media is a pragmatic competitor to achieve financial profit targets. The latest aspect of this research is that investors in achieving power not only use and control their media, but also more than that, they also intervene in the competitors' media. The inter-media ownership interventions became a new model when media investors in Indonesia expanded in the political arena.